Adverse Effects of the Apolipoprotein E ε4 Allele on Episodic Memory, Task Switching and Gray Matter Volume in Healthy Young Adults - Nao, Jianfei; Sun, Hongzan; Wang, Qiushi; Ma, Shuang; Zhang, Shuo; Dong, Xiaoyu; Ma, Ying; Wang, Xiaoming; Zheng, Dongming (Frontiers in Human Neuroscience, 2017)
Many studies have shown that healthy elderly subjects and patients with Alzheimer’s disease (AD) who carry the apolipoprotein E (ApoE) ε4 allele have worse cognitive function and more severe brain atrophy than non-carriers. However, it remains unclear whether this ApoE polymorphism leads to changes of cognition and brain morphology in healthy young adults. In this study, we used an established model to measure verbal episodic memory and core executive function (EF) components (response inhibition, working memory and task switching) in 32 ApoE ε4 carriers and 40 non-carriers between 20 and 40 years of age. To do this, we carried out an adapted auditory verbal learning test and three computerized EF tasks. High-resolution head magnetic resonance scans were performed in all participants and voxel-based morphometry (VBM) was used for image processing and analysis. Multivariate analysis of variance performed on memory measures showed that the overall verbal episodic memory of ApoE ε4 carriers was significantly worse than non-carriers (Wilk’s λ = 4.884, P = 0.004). No significant differences were detected in overall EF between the two groups. Post hoc analyses revealed group differences in terms of immediate recall, recognition and task switching, which favored non-carriers. VBM analysis showed gray matter (GM) bilateral reductions in the medial and dorsolateral frontal, parietal, and left temporal cortices in the carrier group relative to the non-carrier group, which were most significant in the bilateral anterior and middle cingulate gyri. However, these changes in GM volume were not directly associated with changes in cognitive function. Our data show that the ApoE ε4 allele is associated with poorer performance in verbal episodic memory and task switching, and a reduction in GM volume in healthy young adults, suggesting that the effects of ApoE ε4 upon cognition and brain morphology exist long before the possible occurrence of AD.